(untitled) (Eurasian Scientific Herald, 2023)
The article presents algorithms for managing dynamic objects based on adaptive filtering methods. A functional diagram of an adaptive system for dynamic control of technological processes is proposed. For the values of the adaptive filter size, the relationship between the sum of squares of the correlation coefficient and the signal error obtained as a result of filtering the original useful signal is obtained. The proposed adaptive control system makes it possible to stabilize the mode of technological parameters of the process, improve the quality of products and the productivity of the unit. These algorithms make it possible to use dynamic production objects in automation and control tasks